Structural basis for the coordination of cell division with the synthesis of the bacterial cell envelope. (30th September 2019) - Booth, Simon; Lewis, Richard J.
Abstract: Bacteria are surrounded by a complex cell envelope made up of one or two membranes supplemented with a layer of peptidoglycan (PG). The envelope is responsible for the protection of bacteria against lysis in their oft‐unpredictable environments and it contributes to cell integrity, morphology, signaling, nutrient/small‐molecule transport, and, in the case of pathogenic bacteria, host–pathogen interactions and virulence. The cell envelope requires considerable remodeling during cell division in order to produce genetically identical progeny. Several proteinaceous machines are responsible for the homeostasis of the cell envelope and their activities must be kept coordinated in order to ensure the remodeling of the envelope is temporally and spatially regulated correctly during multiple cycles of cell division and growth. This review aims to highlight the complexity of the components of the cell envelope, but focusses specifically on the molecular apparatuses involved in the synthesis of the PG wall, and the degree of cross talk necessary between the cell division and the cell wall remodeling machineries to coordinate PG remodeling during division. The current understanding of many of the proteins discussed here has relied on structural studies, and this review concentrates particularly on this structural work.